Implementation of an integrated system of reproductive technology and management in a breeding cattle in the central semi-arid zone in the province of La Pampa (Veterinary Science, 2019)
The beef cattle rearing is an economic and social activity in La Pampa province, developed in an area of natural forages, with severe weather and edaphic limitations. The present trial was carried out on a beef farm with 320 British crossbreed cattle, at Toay Department, LaPampa. During a period of five years, a protocol as following was implemented: three-time estrous synchronization followed by fixed-time artificial insemination plus natural mating until the end of the breeding period. The protocol used for artificial insemination started 40 days post-partum and each cow was classified by a colour ear tag and by probable date of delivery. At day zero, an intra-vaginal progesterone dispositive (0.5 g, i.v., Dib, Sintex S.A., Argentina) was placed to all cows in combination with an estradiol benzoate dose, when the dispositive was removed, after 7 days, the animals received a dose of prostaglandin (Cloprostenol, 2 cc., i.m., Ciclase DL, Sintex S.A.) and estradiol cypionate (1 mg, i.m. Cipiosyn, Sintex S.A., Argentina), to finally be inseminated at day 9. Thereafter, the protocol finished with the incoming of 5% of bulls until the end of the predetermined breeding period. The pregnancy percentage of both cows and heifers increased through the study period to values of 90 and 91%, respectively. 70% of parturition was concentrated during the first month, 23% in the second and just 3% during the last month of calving season. The  suggested system allows increasing the reproductive efficiency of the cattle herd, achieving both a higher percentage of early pregnancy and increasing interparturition interval allowing a better recovery of the reproductive tract.
Keywords: Eficent Breed; Caldenal Zone; Anoestrous post-partum; IATF